The Effects of Storage in vitro on Functions, Transcriptome, Proteome, and Oxidation Resistance of Giant Grouper Sperm - Yang, Yang; Wang, Tong; Yang, Sen; Wu, Xi; Huang, Wenhua; Fan, Bin; Xia, Junhong; Meng, Zining; Liu, Xiaochun (Frontiers in Marine Science, 2021)
Asynchrony of sexual maturity is a huge limit in reproduction of grouper. Sperm storage in vitro is an effective method to solve the problem. However, Sperm gradually lost their activity with the lasting storage time in vitro. For exploring causes, the effects of cold storage on transcriptome, proteome and oxidation resistance of giant grouper sperm were analyzed. Firstly, the absolute RNA quantity and consistent transcripts existed in each spermatozoon were estimated. With the lastingness of storage, the RNA quantity gradually decreased both in cytoplasm and mitochondria of spermatozoon. The decreased transcripts were mainly enriched into energy metabolism and stress response pathways. Similar to RNAs, the absolute protein quantity also significantly decreased during storage in sperm. Decreased proteins were mainly enriched into oxidative phosphorylation pathway. Proteins involved in oxidative phosphorylation showed a faster degradation rate comparing total protein’s average. In addition, oxidation resistance and ATP contents showed a significant decreased in sperm during storage in vitro. These results implied that damages of transcriptome, proteome and oxidation resistance have negative effects on normal functions in sperm, especially energy metabolism. The present studies provided essential foundation for improving sperm storage in vitro.